Effect of probiotic supplementation on wound healing in postoperative patients: A case report and literature review - Cut Thalya Alissya Rahma; Yohanessa Wulandari (World Nutrition Journal, 2023)
Background: Delayed wound healing, particularly in chronic wounds, is a significant global public health issue. The World Health Organization (WHO) reports that over 6 million people in the United States experience delayed wound healing annually, resulting in a healthcare cost of $25 billion USD. Probiotics, known for their anti-inflammatory properties, have potential in influencing skin immunity by facilitating the transfer of cytokines and immune cells from Peyer's patches to the skin. Nevertheless, the precise impact of probiotics on postoperative wound healing remains an area with limited research. Objective: Determine the effectiveness of probiotic supplements in wound healing in patients with surgical wounds Method: Literature search is done by advanced searching on Pubmed, Cochrane, Scopus, and EBSCOhost with eligibility criteria determined by the author. Results: There were three articles relevant to clinical questions and eligibility criteria that had been established, consisting of one systematic review article from the randomized controlled trial (RCT) study and two RCT articles. The SR/MA article includes good-quality RCT studies. The SR/MA article showed insignificant results on the effect of probiotic administration on healing. The RCT article showed significant results on the effect of probiotics on surgical wound healing, but the confidence level was low in one of the articles. Conclusion: Probiotic supplementation on wound healing in postoperative patients is not conclusive. This can be affected by the type of probiotic strain, dosage, duration of administration, and location of the surgical wound.